Marine and Coastal Resources Governance Issues in Casamance, Senegal: Example of MPAs - Soda Loum; Mamadou Thior; Issa Sakho; Michel Desse (European Scientific Journal, ESJ, 2022)
The maritime space of Casamance (south of Senegal), like everywhere in the West African coast has become a territory of competition for projects on both local and international scales. This competition appears in different forms and affects several sectors (fishing, tourism, real property, mining, etc.). These different actors have developed forms of competition that are poorly circumscribed by public policies, thus leading the State of Senegal to resort to marine protected areas (MPAs). Moreover, the governance of Marine Protected Areas has become a trend thanks to its participatory approach highlighting the common desire to preserve marine and costal natural resources. In this work, we studied the role of Protected Areas in the regulation of tensions around marine and coastal resources in Casamance. The approach is based on the review of documents (scientific and strategic policies, etc.), and field training on the protected areas of Casamance. The results shown that the MPAs are an excellent governance strategy and have led to better conservation of marine and coastal resources in Casamance.